Biotic Potential and Life Tables of Chrysodeixis includens (Lepidoptera: Noctuidae), Rachiplusia nu, and Trichoplusia ni on Soybean and Forage Turnip. Issue 4 (12th July 2019) - Specht, Alexandre; Sosa-Gómez, Daniel Ricardo; Roque-Specht, Vânia Ferreira; Valduga, Eduardo; Gonzatti, Felipe; Schuh, Sabrina Maurer; Carneiro, Eduardo
Abstract: Loopers such as Chrysodeixis includens (Walker), Rachiplusia nu (Guenée), and Trichoplusia ni (Hübner) are important defoliators in soybean, sunflower, and crucifer crops, respectively, in countries of the Americas. The biotic potential of these polyphagous species of Plusiinae was comparatively examined considering crop rotation and succession scenarios in which crucifer crops are cultivated during or after Brazilian winter. All the species developed and reproduced on soybean (BRS 133 Embrapa) and forage turnip (Cati AL 1000, Wolf Seeds do Brasil). The development of C. includens was similar on both host plants. The survival of R. nu was lower on forage turnip than on soybean. In contrast, T. ni performance (survival, fecundity, pupal weight) was better on forage turnip than on soybean. This suggests that in crop rotation and succession scenarios of soybean after brassicacea, C. includens is likely to have a higher number of generations per year and could be potentially more harmful.